Visualising slavery : art across the African diaspora - Bernier, Celeste-Marie; Durkin, Hannah (Liverpool studies in international slavery, 2016)
This book adopts a comparative and interdisciplinary perspective to investigate the experimental bodies of works produced by African, African American, African Caribbean and Black British artists in order to excavate and theorise the formal and thematic contours of an African Diaporic visual arts tradition.